The role of digital financial literacy on financial well-being with financial technology, financial confidence, financial behavior as intervening and sociodemography as moderation - Abdurrahman, Abdurrahman; Nugroho, Dimas Adi (Jurnal Ekonomi dan Bisnis, 2024)
Digital financial literacy is a prerequisite for effective use of financial technology. A person can utilize digital financial services properly if they understand digital finance well. Digital financial literacy has a positive financial behavior impact and has more financial confidence, so individuals can build financial resilience to achieve financial well-being. This study explores the effect of digital financial literacy on financial well-being and the interaction between financial technology, financial confidence, financial behavior, and sociodemographic. This study uses the purposive random sampling data collection method, processed using the LISREL application. There were 356 adult age group respondents aged ≥ 18 years in this study. This study found that financial technology, financial behavior, and financial well-being are directly influenced by digital financial literacy; financial behavior is directly influenced by financial confidence and financial technology; financial well-being is influenced by financial confidence and financial behavior; and sociodemographic moderation does not strengthen the influence of digital financial literacy on financial technology. Through these results, it is essential to increase digital financial literacy to improve financial well-being by adopting financial technology and increasing financial confidence and behavior.